Protective effect of citrus honey toward the histopathological and biochemical nephrotoxicity damages of gentamicin–induced in local rabbits Oryctolagus cuniculus - Riyam Ameen Salih; Abdul–Karim Salim Mahood; Samira Abdul-Hussain Abdulla; Mohammed Abdullah Ajeel (Tikrit Journal of Pure Science)
Drugs induced nephrotoxicity now considered as an essential reason for kidney failure. Aminoglycoside anti-infection agents, for example, gentamicin, which causes ototoxicity and nephrtotoxicity as a side effect , this research is centered around the utilization of natural materials as an antioxidants against the lethal oxidative activity that applied on the kidney cells ,the most imperative one of these materials is the honey. This work aimed to assess the defensive impact of citrus honey against the histopathological and biochemical harms of gentamicin induced nephrotoxicity .24 locally breed rabbits (Oryctolagus cuniculus) were used and divided into 4 study groups (6 rabbits per each group), group 1 received I.P daily dose of normal saline (control), group 2 received (80 mg/kg/day) I.P dose of gentamicin, group 3 received (80mg/kg/day) of gentamicin I.P dose in combination with oral dose of Citrus Honey625 mg/kg/day for 14 days and group 4 received (80mg/kg/day) of gentamicin I.P dose in combination with extra dose of Citrus Honey orally for 14 days. All animals (at 15th day) were anesthetized by ether and sacrificed; blood samples were gathered for the subsequent measurement of the serum creatinine, urea and albumin  while an isolated kidney was kept in 10 % of formaldehyde for the histopathological examination. The results demonstrated that gentamicin causes nephrotoxicity showen by elevation of serum level of creatinine, urea and  a decrease in the serum albumin. While the administration of honey in combination with gentamicin reduced the nephro-toxic effect of gentamicin that represented by a reduction of the serum creatinine and urea with improvement of the kidney histological findings.This study concluded that, honey decreased nephrotoxic effect of  gentamicin.